2018
DOI: 10.1038/s41598-018-19670-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen reduces inflammation, oxygenates injured muscle, and regenerates skeletal muscle via macrophage and satellite cell activation

Abstract: Hyperbaric oxygen treatment (HBO) promotes rapid recovery from soft tissue injuries. However, the healing mechanism is unclear. Here we assessed the effects of HBO on contused calf muscles in a rat skeletal muscle injury model. An experimental HBO chamber was developed and rats were treated with 100% oxygen, 2.5 atmospheres absolute for 2 h/day after injury. HBO reduced early lower limb volume and muscle wet weight in contused muscles, and promoted muscle isometric strength 7 days after injury. HBO suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 41 publications
1
45
0
5
Order By: Relevance
“…The gene set of "negative regulation of immune response" was enriched in HBO group suggesting an inflammation inhibition effect too. The immune inhibition information we get from the DEG analysis and GSEA are consistent with the reduction in lipofibroblasts, which characteristically show activation of inflammation, and consistent with the reports that HBO exposure attenuate inflammation in a few of conditions [56][57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 89%
“…The gene set of "negative regulation of immune response" was enriched in HBO group suggesting an inflammation inhibition effect too. The immune inhibition information we get from the DEG analysis and GSEA are consistent with the reduction in lipofibroblasts, which characteristically show activation of inflammation, and consistent with the reports that HBO exposure attenuate inflammation in a few of conditions [56][57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 89%
“…Subsequently, the laminin is re-formed, and the abnormal proliferation of blood vessel cells ceases. The blood vessels then become mature, and angiogenesis is completed at 7 to 14 days 13,32 . In the HBO group in the present study, the number of proliferating endothelial cells was increased at 1 day after injury, and then the number of immature vessels increased at 3 days and decreased from 5 days after injury.…”
Section: Discussionmentioning
confidence: 99%
“…HBO has been reported as an additional treatment for skeletal muscle injury, as HBO is clinically considered to promote muscle regeneration 28,29 and accelerate the return to competition 30 . Our previous study showed that HBO accelerated the recovery of intact muscle volume, stimulated satellite cell proliferation, and promoted muscle regeneration via macrophage recruitment 31,32 . In a previous study, HBO increased mRNA levels of bFGF and HGF without upregulation of VEGF, increasing and promoted angiogenesis and muscle regeneration after ischemic muscle injury 6 .…”
mentioning
confidence: 99%
“…According to the team of Yagishita, STAT3 phosphorylation is a major step in satellite cell activation and tissue repair. Whether in diabetic patients, the progenitor cell activation contributes toward wound healing and conservation of cardiovascular status, needs to be further assessed [35].…”
Section: Discussionmentioning
confidence: 99%